Comparison of a Preservative-free Non-steroidal Anti-inflammatory Drug and Preservative-free Corticosteroid after Uneventful Cataract Surgery: A Randomized Control Trial - Alam, Md Toriqul; Anwar, Md Towhid; Chowdhury, Kousik; Aktar, Nasima; Rahman, Md Munsur; Md Munir, Iftekhar (Journal of National Institute of Ophthalmology, 2022)
Background: Cataract is considered as a main cause of blindness around the world along with glaucoma and macular degeneration. Now, surgery remains the only effective treatment option of cataracts and cataract surgery is one of the most frequently accomplished surgeries in the field of ophthalmic arena. This study aimed to compare the effects of NSAIDs with those of steroids for the management of inflammation after uneventful cataract surgery. Methods: This study was a prospective randomized control trial, conducted at the Department of Cataract in National Institute of Ophthalmology and Hospital, Dhaka, from 01 February 2021- 30 January 2022. A total of 194 patients were randomly allocated into two groups by lottery. The patients of NSAID group was prescribed bromfenac sodium hydrate 0.1% to apply two times a day in 1 eye, whereas the steroid group was treated with Dexamethasone 0.1%, 4 times per day for 4 weeks after the surgery. Results: The mean age of the patients in NSAID and steroid group were 71.10 (± 8.55) years and 72.09 (± 8.64) years respectively. The male female ratio of each group was 33:64. The change in inflammation grade of the anterior from postoperative day 1 to week 8 in the NSAID group was -1.25 ± 1.30 and in the steroid group -1.25 ± 1.32 which shows a significant reduction in both eyes (p <0.001). Comparing the changes from preoperative to week 1 and preoperative to week 8 showed central corneal thickness in the NSAID group was also significantly less than that in the steroid group (8.87 ± 22.46 and 29.48± 46.60 vs. 4.74 ± 31.75 and 8.76 ± 40.95 mm) (p<0.05). Comparing the changes from postoperatively to week 1 and postoperatively to week 8, the NSAID group had lower conjunctival hyperemia -0.09± 0.53 and -0.19 ± 0.54 vs. the steroid group had higher conjunctival hyperemia 0.08 ± 0.64 and -0.20 ± 0.53. Conclusion: NSAIDs like nepafenac 0.1%, bromfenac 0.09%, and ketorolac 0.5% are proven to be a good alternative to steroids which has a corresponding level of anti-inflammatory activity like Dexamethasone 0.1% for controlling postoperative ocular inflammation among patients going through cataract surgery. J. Natl. Inst. Ophthalmol. 2022;5(1):10-15